#TITLE_ALTERNATIVE# - Abduh (NIM 250 94 067), Muhamad
Abstract: The use of High Performance Concrete (HPC) in the construction industry has increased significantly in the last few years. However, information regarding its mechanical properties is still lacking, especially information on its shielding properties under gamma radiation. Knowledge on these properties is necessary for promoting the application of HPC as construction material for nuclear power plant. The objective of this research is to study HPCs attenuation coefficient under 0,661 MeV gamma radiation of Cs-137. Two types of HPC are evaluated, i.e. Fly ash High Strength Concrete (HSC) that has compressive strength of 42-50 MPa and Polymer HSC with compressive strength of 60 MPa. As reference in evaluating the test results, normal concrete with 30 MPa compressive strength is also tested in this study. Curing period for concrete with Fly Ash is 7 and 28 days, while curing period for other concrete is 28 days. The test parameters investigated in this experimental study are the relationships between concrete density and attenuation characteristic of the concrete, and the effect of irradiation on temperature rise and its distribution, thermal stress generation and micro-structure damage of the concrete. The results of the experimental study and analysis conclude that concrete density increases while the compressive strength of the concrete increases. The result of attenuation experiment shows that the attenuation capability of the concrete can be increased by increasing its density, using Fly Ash HSC and Polymer HSC, and reducing the concrete voids. The other results indicate that Polymer HSC has lesser void ratio (9,9767 percent) than concrete with fly ash (12,5142percent) and than normal concrete (14,3508percent). Polymer HSC also has the lowest density (2,1855 g/cm3), highest compressive strength (61 MPa) and a potential becoming the best alternative material for radiation shielding; Its attenuation coefficient is higher 1,5 times than Fly Ash HSC and 1,6 times than normal concrete. Due to gamma irradiation, there is 0,65 - 0,85degreeC temperature rise in Fly Ash HSC and 0,6 - 0,9degreeC in normal concrete. The temperature distribution generates 0,16 MPa thermal stress in the Fly Ash HSC, otherwise there is no change in thermal stress in normal concrete.